2021
DOI: 10.1002/smll.202006970
|View full text |Cite|
|
Sign up to set email alerts
|

Cytosolic Delivery of Thiolated Mn‐cGAMP Nanovaccine to Enhance the Antitumor Immune Responses

Abstract: As a stimulator of interferon gene (STING), cyclic dinucleotide activates a broad cellular immune response for anti‐cancer immunotherapy (CIT). However, the inherent of instability of 2′ 3′‐cyclic‐GMP‐AMP (cGAMP) with poor cellular targeting, rapid clearance, and inefficient transport to the cytoplasm seriously hinders cGAMP potency. Here, a thiolated and Mn2+ coordinated cyclic dinucleotide nanovaccine (termed as Mn‐cGAMP NVs) to enable direct cytosolic co‐delivery of cGAMP and Mn2+ to potentiate the antitumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Several research groups have already begun to develop nanotechnology and/or depots for Mn 2+ delivery to promote enhanced pharmacological STING pathway activation for cancer immunotherapy. , Wang et al reported a biomaterial-based delivery approach that coupled the divalent cation chelator alginate with Mn 2+ in the context of radiotherapy . The researchers found that intratumoral injections of Mn 2+ by itself could indeed enhance the antitumor immune response following RT but that the timing of administration was critical for efficacy.…”
Section: Therapeutic Potentiators Of the Sting Pathwaymentioning
confidence: 99%
“…Several research groups have already begun to develop nanotechnology and/or depots for Mn 2+ delivery to promote enhanced pharmacological STING pathway activation for cancer immunotherapy. , Wang et al reported a biomaterial-based delivery approach that coupled the divalent cation chelator alginate with Mn 2+ in the context of radiotherapy . The researchers found that intratumoral injections of Mn 2+ by itself could indeed enhance the antitumor immune response following RT but that the timing of administration was critical for efficacy.…”
Section: Therapeutic Potentiators Of the Sting Pathwaymentioning
confidence: 99%
“…Potassium (K + ) preserves T-cell stemness and increases persistence and potency of T-cells 28 . In particular, recent studies have shown that Mn 2+ sensitizes the cGAS-STING pathway to double-stranded DNA during DNA virus infection 34 and synergizes with immune checkpoint inhibitors 37 , chemotherapy 38 , in-situ vaccine 39 , and photodynamic therapy 40 . However, despite their promise, it remains largely unknown how to systemically develop an effective metalloimmunotherapy and deliver them in appropriate pharmaceutical forms.…”
mentioning
confidence: 99%
“…Synergistic modulation of multiple immune signaling pathways of APCs is a promising way to enhance neoantigen cross-presentation. Accordingly, CpG-oligodeoxy­nucleotides (CpG-ODN), Toll-like receptor 9 (TLR9) agonists, have shown potent immuno­stimulatory properties by enhancing cross-presentation of APCs through increasing expression of MHC-II, CD86/80 molecules, and Type I interferon under the existence of antigens to elicit innate immunity. Moreover, synergistic activation of stimulator of interferon gene (STING) pathway and TLR9 pathway to induce strong Th1-type responses, enhanced IFN-γ production, and cytotoxic CD8+T-cell responses could more efficiently boost cancer immunotherapy. , However, the short-term activation of APCs through single bolus injection within 2 days is not enough to provide long durability of immune protection. , Recent works designed injectable PNP-gels to prolong the codelivery of antigen/adjuvant to create a local inflammatory niche for enhancing the magnitude and duration of germinal center responses with a unique kinetics. Comparably, silk-gel may enact as an ideal vector system for biomedical applications due to its biocompatible and biodegradable properties without immunogenicity and cytotoxicity, and it has been extensively used as a surgical suture and an absorbable surgical mesh in the clinic for a long history. …”
Section: Resultsmentioning
confidence: 99%
“…20,26−28 However, the short-term activation of APCs through single bolus injection within 2 days is not enough to provide long durability of immune protection. 29,30 Recent works designed injectable PNP-gels to prolong the codelivery of antigen/adjuvant to create a local inflammatory niche for enhancing the magnitude and duration of germinal center responses with a unique kinetics. 31−39 Comparably, silk-gel may enact as an ideal vector system for biomedical applications due to its biocompatible and biodegradable properties without immunogenicity and cytotoxicity, and it has been extensively used as a surgical suture and an absorbable surgical mesh in the clinic for a long history.…”
mentioning
confidence: 99%